2016
DOI: 10.1136/bjsports-2015-095829
|View full text |Cite
|
Sign up to set email alerts
|

Health conditions detected in a comprehensive periodic health evaluation of 558 professional football players

Abstract: Dette er siste tekst-versjon av artikkelen, og den kan inneholde små forskjeller fra forlagets pdf-versjon. Forlagets pdf-versjon finner du på bjsm.bmj.com: http://dx.doi. org/10.1136/bjsports-2015-095829 This is the final text version of the article, and it may contain minor differences from the journal's pdf version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 58 publications
1
35
1
3
Order By: Relevance
“…We analysed prospectively collected data from a PHE of professional male football players in Qatar 15. All players eligible to compete in the Qatar Stars League (QSL), the professional first division of football in Qatar, were invited to participate as they presented for their annual PHE at Aspetar Orthopaedic and Sports Medicine Hospital in Doha (Qatar) at the beginning of the 2013 and 2014 seasons, which the majority (66.6%) completed during the preseason period (July through September).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analysed prospectively collected data from a PHE of professional male football players in Qatar 15. All players eligible to compete in the Qatar Stars League (QSL), the professional first division of football in Qatar, were invited to participate as they presented for their annual PHE at Aspetar Orthopaedic and Sports Medicine Hospital in Doha (Qatar) at the beginning of the 2013 and 2014 seasons, which the majority (66.6%) completed during the preseason period (July through September).…”
Section: Methodsmentioning
confidence: 99%
“…After the completion of the initial 9+ in 2013, a report form with the total 9+ score along with the results from the other PHE tests was given to the respective team doctor 15. Other than that, no specific intervention was advised based on the 9+ score from test 1.…”
Section: Methodsmentioning
confidence: 99%
“…While predicting future injury risk through screening tests is unrealistic, a PHE or pre-participation examination can serve several other purposes, as outlined in the the IOC consensus statement on periodic health evaluation of elite athletes 37. First and foremost, it includes a comprehensive assessment of the athlete's current health status, and, typically, it is the entry point for medical care of the athlete.…”
Section: Should We Discontinue Phes?mentioning
confidence: 99%
“…As demonstrated by Bakken and colleagues,19 in a large cohort of professional football players, the majority of athletes presented with at least one current health condition and one in three with a musculoskeletal condition requiring some form of follow-up. Other potential benefits of regular health examinations include establishing rapport between the medical team and the athlete, reviewing medications and supplements to avoid inadvertent doping, establishing a performance baseline for the athlete in the healthy state, and, in some settings, to satisfy the medicolegal duties of care 37. Nevertheless, the IOC consensus statement concluded that large-scale population-based studies are needed to evaluate the components of history and examination that can be used to identify athletes at risk, intervene and change outcome, and recommended that programmes on PHEs be set up and conducted as research projects.…”
Section: Should We Discontinue Phes?mentioning
confidence: 99%
“…As pointed out in my recent review,2 as well as in the 2009 International Olympic Committee consensus paper on periodic health evaluation of elite athletes,3 athlete screening can serve many purposes. Perhaps the most important of these is to assess an athlete's current health status, that is, detect current injury or illness, as recently shown in a large, prospective study by Bakken et al 4. However, importantly, predicting injury based on screening tests is not one of them, as outlined in my paper 3…”
mentioning
confidence: 92%